2013
DOI: 10.1155/2013/752852
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and Susceptibility to Infectious Diseases

Abstract: To summarize the literature regarding susceptibility of pregnant women to infectious diseases and severity of resulting disease, we conducted a review using a PubMed search and other strategies. Studies were included if they reported information on infection risk or disease outcome in pregnant women. In all, 1454 abstracts were reviewed, and a total of 85 studies were included. Data were extracted regarding number of cases in pregnant women, rates of infection, risk factors for disease severity or complication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
142
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 247 publications
(159 citation statements)
references
References 87 publications
2
142
0
6
Order By: Relevance
“…Also possible influence of gestation, as being a factor in finding HSV-1, needs to be addressed as our results show that most of the HSV-1-DNA-positive mothers were positive before delivery ( Figure 2). It has been shown that genital HSV recurrences increase during pregnancy even though clinical manifestations of infection seem to remain as similar as in non-pregnant women [31]. Taken together, HSV-1 shedding into oral cavity is frequent in HSV-1 carriers, even for a very short duration.…”
Section: Discussionmentioning
confidence: 95%
“…Also possible influence of gestation, as being a factor in finding HSV-1, needs to be addressed as our results show that most of the HSV-1-DNA-positive mothers were positive before delivery ( Figure 2). It has been shown that genital HSV recurrences increase during pregnancy even though clinical manifestations of infection seem to remain as similar as in non-pregnant women [31]. Taken together, HSV-1 shedding into oral cavity is frequent in HSV-1 carriers, even for a very short duration.…”
Section: Discussionmentioning
confidence: 95%
“…Meningitis due to Listeria has been ranked at third position among the bacterial causes of meningitis in humans (Koopmans et al 2014). Young ones, especially newborns, elderly persons, pregnant women, immunocompromised and immunologically immature individuals are generally at higher risk to acquire listeriosis (Mart ınez-Montero et al 2013 ;Poulsen & Czuprynski 2013;Sappenfield et al 2013). Serious implications such as septicaemia, meningitis and gastroenteritis occur in newborns/neonates, elderly and immunocompromised people with case fatality rates of 30%À40% (Barbuddhe, Malik, et al 2008;Vera et al 2013).…”
Section: Public Health Concernsmentioning
confidence: 99%
“…1). Так, среднемноголетний показатель забо-леваемости ОРВИ в педиатрических отделениях соста-вил 176,6 на 1000 пациентов [95% ДИ 171, 7] (удельный вес в общей структуре от 62,4% до 70,5% по годам), превысив в 3 раза данный показатель в хирур-гических отделениях -59,16 на 1000 [95% ДИ 56,63-61,69] и в 11,5 раз выше, чем в ОРИТ -15,4 на 1000 пациентов [95% ДИ [10][11][12][13][14][15][16][17][18][19][20]8]. Причинами та-кого соотношения являлись: более высокий процент за-носов инфекции в педиатрические отделения (73,6 -79,6% в структуре заболеваемости); 20-23% состави-ли больные изоляционно-диагностического отделения (в котором изолируются больные ОРВИ); большая про-должительность стационарного лечения пациентов в пе-диатрических отделениях, чем в хирургических, что уве-личивало риск внутрибольничного инфицирования.…”
Section: результаты и их обсуждениеunclassified
“…Согласно данным литературы, из широкого много-образия респираторных вирусов (более 200) ведущими возбудителями ОРВИ являются вирусы гриппа, параг-риппа, аденовирусы, риновирусы, респираторно-син-цитиальный вирус (РС-вирус), имеющие особое значе-ние среди детей, а также коронавирусы, реовирусы, эн-теровирусы, бокавирусы, метапневмовирусы, увеличи-вается роль вирусных ассоциаций [9][10][11].…”
unclassified